2004
DOI: 10.1152/ajpgi.00090.2004
|View full text |Cite
|
Sign up to set email alerts
|

Enteroendocrine cells and 5-HT availability are altered in mucosa of guinea pigs with TNBS ileitis

Abstract: Enteroendocrine cells act as sensory transducers, releasing 5-HT and numerous peptides that are involved in regulating motility, secretion, and gut sensation. The action of mucosal 5-HT is terminated by a 5-HT reuptake transporter (SERT). In this study, we examined the hypothesis that ileitis leads to changes in enteroendocrine cell populations and mucosal 5-HT availability. Ileitis was induced in guinea pigs by intraluminal injection of 2,4,6-trinitrobenzenesulfonic acid and experiments were conducted 3, 7, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
114
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 53 publications
11
114
1
3
Order By: Relevance
“…Recent reports have confirmed the relevance of the SERT function for the control of intestinal activity [30,31]. SERT expression and activity are affected in intestinal inflammation [10,[14][15][16] and inflammatory mediators have been shown to inhibit SERT function and expression in epithelial cells [12,13].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Recent reports have confirmed the relevance of the SERT function for the control of intestinal activity [30,31]. SERT expression and activity are affected in intestinal inflammation [10,[14][15][16] and inflammatory mediators have been shown to inhibit SERT function and expression in epithelial cells [12,13].…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies have concluded that the alteration of the GI serotoninergic system may be involved in the origin and/or prevalence of chronic GI pathologies such as Irritable Bowel Syndrome (IBS) and Inflammatory Bowel Disease (IBD) [10,11]. Recent results have demonstrated that SERT expression is downregulated and SERT activity is impaired in intestinal epithelial cells treated with pro-inflammatory factors [12,13], in animal models and human forms of intestinal inflammation [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados observados por O` Hara et al (2004) indicam que a recaptação de serotonina é realmente reduzida durante a inflamação por Citrobacter rodentium, onde as células imunomarcadas para SERT foram reduzidas 10 dias após a infecção. Mesmos resultados foram observados em colites ulcerativas em humanos (Coates et al 2004).…”
Section: Discussionunclassified
“…The mucosal mast cells may therefore function as an expulsion system of intestinal nematode infections. In recent, O'Hara et al (2004) presented evidence that enteroendocrine cells and serotonin availability in intestinal mucosa were altered in experimental ileitis. This indicates that pathological changes in the transduction pathway between mucosal endocrine cells and primary afferent nerve terminals may lead to decreased motility and secretion in irritable bowel diseases.…”
Section: Discussionmentioning
confidence: 99%